2019
DOI: 10.1101/2019.12.13.875369
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glucose starvation to rapid death of Nrf1, but not Nrf2, deficient hepatoma cells from its fatal defects in the redox metabolism reprogramming

Abstract: Metabolic reprogramming exists in a variety of cancer cells, with the most relevance to glucose as a source of energy and carbon for survival and proliferation. Of note, Nrf1 was shown to be essential for regulating glycolysis pathway, but it is unknown whether it plays a role in cancer metabolic reprogramming, particularly in response to glucose starvation.Herein, we discover that Nrf1α / -derived hepatoma cells are sensitive to rapid death induced by glucose deprivation, such cell death appears to be rescu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 60 publications
7
9
0
Order By: Relevance
“…In NFE2L1 knockdown cells, the ROS level was increased more than 6 times in comparison with the control group after glucose deprivation for 6 hours, indicating the high levels of oxidative damage of NFE2L1 knockdown cells. These results were in accordance with previous studies that glucose starvation resulted in strong oxidative stress to induce cell death after NFE2L1 knockout (Qiu et al, 2018; Zhu et al, 2020).…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…In NFE2L1 knockdown cells, the ROS level was increased more than 6 times in comparison with the control group after glucose deprivation for 6 hours, indicating the high levels of oxidative damage of NFE2L1 knockdown cells. These results were in accordance with previous studies that glucose starvation resulted in strong oxidative stress to induce cell death after NFE2L1 knockout (Qiu et al, 2018; Zhu et al, 2020).…”
Section: Resultssupporting
confidence: 94%
“…Consistent with our results, previous studies had shown that overexpression and knockout of NFE2L1 could change glucose metabolism through different ways such as ROS, insulin secretion, and liver metabolism (Hirotsu et al, 2014; Zheng et al, 2015; Zhu et al, 2020). However, the underlying molecular mechanism by which NFE2L1 affects glucose metabolism remains to be explored.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Represented by glycolysis, fatty acid oxidation, and amino acid metabolism, metabolic reprogramming is a typical hallmark in cancer cells [50]. Tumor cells are featured by the strong dependence on glycolysis to provide energy despite sufficient oxygen availability [51].…”
Section: Regulation Of Tumor Metabolismmentioning
confidence: 99%